Association of neutrophil to high-density lipoprotein cholesterol ratio with overactive bladder: a population-based study - Zhang, Huifeng; Xu, Yaying; Chen, Lele (Frontiers in Endocrinology, 2025)
BackgroundInflammation is involved in the progression of overactive bladder (OAB). This study aimed to investigate the association between the neutrophil to high-density lipoprotein cholesterol ratio (NHR) and OAB.MethodsData from seven cycles of the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018 were analyzed to examine the relationship between NHR and OAB. Multivariable logistic regression model was used to estimate the association between NHR and OAB, along with restricted cubic spline regression to assess the dose-response relationship. Additionally, subgroup analyses were conducted.ResultsAmong 29,315 participants, 5,815 had OAB. After covariate adjustment, we found that NHR was positively associated with the odds of OAB. Notably, the relationship between NHR and OAB was nonlinear. There was a threshold at NHR = 2.85. When NHR < 2.85, no significant association was observed; when NHR ≥ 2.85, a positive association emerged. Subgroup and interaction analyses further revealed that the link between NHR and OAB was stronger in obese participants.ConclusionOur results indicate a nonlinear association between NHR and OAB. When NHR is ≥ 2.85, there is a strong positive association between NHR and the odds of OAB. The interaction between obesity and NHR further increases the prevalence of OAB. Prospective and multicenter studies are needed in the future to elucidate the potential mechanism underlying the association between NHR and OAB and determine the causal relationship.